Perbandingan Metode SAW, WP, Dan TOPSIS Dalam Pemilihan Rumah Kost Mahasiswa Di Pontianak - Shendy Nurhidayat; Alfi Maulana; Wisnu Gama Kusuma; Perani Rosyani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The number of factors that must be taken into account and considered in making a decision is one of the problems that exist and must be faced by decision makers. This is also the case with students who are going to rent a boarding house. Many factors must be considered and taken into account by students in choosing a boarding house, including the distance from the boarding house to the campus, the distance from the main road to the campus, the size of the room, security, curfew restrictions, rental prices and the type of boarding house. To overcome existing problems, To assist in determining the decision making, a Decision Support System (DSS) approach is used. The criteria used include: location, price, facilities, room size, security. This study aims to analyze the results of the Simple Additive Weighting (SAW), Weighted Product (WP) and Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) methods so that it can be determined which method is more relevant to be implemented in the case of selecting student boarding houses. This research will discuss the process of selecting student boarding houses by analyzing three methods, namely the Simple Additive Weighting (SAW) method, the Weighted Product (WP) method and the Technique for Order of Preference by Similarity to Ideal Solutions (TOPSIS method). Although in general the three methods are relatively equally relevant.